PELATIHAN TATA KELOLA ADMINISTRASI PEMERINTAHAN DESA BERBASIS DIGITAL DI KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Sartono, Sartono; Muhammad Elwan, La Ode; Jopang, Jopang; Qomariyah, Erni; Yusuf, Muh.; Liwaul, Liwaul; Taufik, Taufik; Aslim, La Ode (Universitas Halu Oleo, 2023)
Ranomeeto District is one of the sub-districts in South Konawe Regency, Southeast Sulawesi Province. The need to implement online-based services as a government system model that is oriented towards the power of digital technology is very important in the current era. All administrative work, services to the community, supervision and control of resources belonging to the institution concerned are controlled in one information technology-based system. The method used in this activity is to provide technical training on digital-based Village government administration in Ranomeeto District, South Konawe Regency. The results of the service show that, on average, webdes in Ranoomeeto District already exist. However, not all of them provide online-based village government administration services (digital transactions) only limited to providing information. The output of this service is the implementation of training for village officials and website operators offline and published in the ISSN Community Service Journal and online news media.